Supercapacitor: Instrumentation, Measurement and Performance Evaluation Techniques - Ratha, Satyajit (SpringerBriefs in Materials,, 2018)
This book discusses the instrumentation of supercapacitors, various measurement procedures and the techniques used for the performance evaluation, to help determine the appropriate methodology for the evaluation of a supercapacitor device and also to identify the inconsistencies between the device performance and electrode material properties. As a promising energy storage option, supercapacitors need to be readied for commercialization rather than confined within the niche of academic research. This book also assists in the formulation of strict performance guidelines aided by realistic evaluation techniques, so that theses devices can be made available to society through industrial production. As such it is an important read not only for academicians and researchers, but also for industry and policymakers.